Risk of ventriculoperitoneal shunt infection with coexisting percutaneous endoscopic gastrostomy tube and associated factors. Issue 3 (March 2020) - Tyler, Kevin; Leon, Stuart M.; Lowe, Stephen; Kellogg, Ryan; Lena, Jonathan; Privette, Alicia R.; Eriksson, Evert A.
Abstract: Objectives: Percutaneous endoscopic gastrostomy (PEG) tubes and ventriculoperitoneal shunts (VPS) are commonly placed in neurologically impaired patients. There is concern about safety of VPS coexisting with PEG tubes due to the potential for an increased risk of infection. In this study, we assess the risk of VPS infection and the amount of time between both procedures. Patients and methods: Retrospective chart review of patients from our institution who had VPS and PEG tubes placed during the same hospitalization between 2014 and 2018. Our primary focus was assessing risk of VPS infection and timing of procedures in this patient population. Additionally, we assessed other factors which may contribute to VPS infection including SIRS criteria at time of VPS placement, comorbidities and other procedures performed. None of the SIRS factors were associated with VPS infection. Results: 45 patients met inclusion criteria. Our VPS infection rate was found to be 7% (n = 3). These patients had 4, 16, and 36 days between procedures. 89% of our patients had PEG tube placed prior to VPS with 2 of these patients developing a VPS infection. At the time of VPS placement 42% of patients had SIRS. None of the SIRS factors were associated with VPS infection. Conclusion: Our VPS infection rate remained low even when they were performed during the same hospitalization as a PEG tube placement. SIRS is not associated with the development of VPS infections and is not an absolute contraindication to placing a VPS. Abstract : Neuroscience; Neurosurgery; Anatomy; Pathology; Critical care; Evidence-based medicine; Ventriculoperitoneal shunt; Infection; Gastrostomy tube; PEG; VP shunt; SIRS; Systemic inflammatory response syndrome.